3 high school teachers from Kuantan create Smart Stroke Lab, combining arts and technology to colour educational innovation, win gold at CITREX UMPSA 2025 - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 1 July 2025 – In an effort to elevate the Visual Arts Education subject while also promoting Science, Technology, Engineering, Arts, and Mathematics (STEAM), a group of teachers from the Kuantan district under the Ministry of Education Malaysia (MOE), led by SMK Bukit Rangin teacher Rizuan Shah Hapipi, developed the Smart Stroke Lab.